Letter - Berks & Oxon Federation of Trades Councils, 5 May 1926 (Oxfordshire)
1926-05-05 "Letter - Berks & Oxon Federation of Trades Councils, 5 May 1926" [g0305001.jpg], 5 May 1926 Local Organisation